Systematic Literature Review: Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) dalam Meningkatkan Keterampilan Berpikir Kritis - Nana, Aljannah Riska; Fajrina, Suci; Arsih, Fitri; Olvia Rahmi, Fitri (Universitas Cokroaminoto Palopo, 2024)
This study aims to develop Student Worksheets (LKPD) based on Problem Based Learning (PBL) which are effective in improving students' critical thinking skills. The PBL method was chosen because it can encourage students to be actively involved in the learning process through solving real problems. This study uses the ADDIE model development approach, which includes analysis, design, development, implementation, and evaluation. The subjects of the study consisted of grade X students in a high school. Data were collected through observation, questionnaires, and critical thinking skills tests before and after the use of LKPD. The results showed that the use of PBL-based LKPD significantly improved students' critical thinking skills. These findings are expected to contribute to the development of more interactive and effective learning methods in the context of education.